PENERAPAN MODEL QUANTUM TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMP NEGERI 5 LUBUK ALUNG - Syofna, Erni; Putra, Atus Amadi; Anggraini, Villia (STKIP PGRI Sumbar, 2013)
There are several background in this research. First, the teacher still dominate all of theaching learning process so that the process applied one way communication or teacher centered. Second, the student are less activity. Third, the students less motivation which affectÂ the understanding of math concept of student especially is grade VIII. The purpose in this research to know whether the understanding of math concept of student by applying the quantum teaching model is better than the understanding of math concept of student by using conventional learning. The kind of this research is experiment by using random subject. Â The population in this research is the student in grade VIII. The sample in this research is grade VIII.3 as experiment class and VIII.4 as control class. The instrument in this research is essay test with reliabilitas = 0,40. The technique of data analysis is used t-test one side, obtained,>Â then the hypothesis in this research is accepted. It is conclude that of math concept of student by applying quantum teaching model is better than the understanding of math concept of student by using conventional learning. Based on data analysis of student can be seen an increasing number of student who are active in every meeting.